Fabricação de filmes ultrafinos no interior de microcanais - Daikuzono, Cristiane Margarete (2013)
The aim here is the fabrication and characterization of nanostructured thin films of different materials inside microchannels to assist the integration process of electronic tongue in lab-on-a-chip devices. The ultrathin films were deposited inside the microchannels using dynamic layer-by-layer technique through copper (II) tetrasulphonated phthalocyanine (CuTsPc) and poly(allylamine hydrochloride) (PAH) bilayers, and also bilayers of poly(3,4-ethylenedioxythiophene) poly(syterenesulfonate) (PEDOT:PSS) and PAH. It was verified the best parameters involved in the nanostructuration of the materials throughout flow and time variations of the deposition of the electrolytes inside the microchannel. Moreover, the growth of the LbL films inside the microchannel was followed by UV-vis and impedance spectroscopy measurements. Through electrical impedance spectroscopy technique was observable that deposition of thin films PAH/CuTsPc was successful using a time of 8 min with a flow of 1500 μL/h, while to films of PAH/PEDOT:PSS optimal time was of 15 min with a static deposition. Raman analyses were used to ascertain of the presence and uniformity of film inside the microchannels. All films of PAH/CuTsPc show good Raman signal, especially those was deposited at 8 min with flow of 500 μL/h. Just films of PAH/PEDOT:PSS deposited in a time great 10 min showed Raman signal; the films deposited at a time of 15 min and flow of 1500 μL/h showed good Raman signal and films more homogeneous. It is worth mentioning that the fabrication of the microchannels and interdigitated electrodes was made in collaboration with Laboratório de Microfabricação do Centro Nacional de Pesquisa em Energia e Materiais (CNPEM) through a specific project in this research line (LMF-13070).